2012
DOI: 10.1111/cogs.12000
|View full text |Cite
|
Sign up to set email alerts
|

Representing Spatial Structure Through Maps and Language: Lord of the Rings Encodes the Spatial Structure of Middle Earth

Abstract: Spatial mental representations can be derived from linguistic and non-linguistic sources of information. This study tested whether these representations could be formed from statistical linguistic frequencies of city names, and to what extent participants differed in their performance when they estimated spatial locations from language or maps. In a computational linguistic study, we demonstrated that co-occurrences of cities in Tolkien's Lord of the Rings trilogy and The Hobbit predicted the authentic longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
(64 reference statements)
1
27
0
Order By: Relevance
“…The idea is simple: Places that are spatially close to each other co-occur together in language, even when the texts in which they co-occur are not spatial in nature per se. And these findings were not limited to existing cities: Locations in fictional Middle Earth were reliably estimated from the novel The Lord of the Rings, with experimental findings indicating that readers of the novel rely on language statistics in their geographical estimates (Louwerse & Benesh, 2012). Similarly, using Arabic and Chinese texts, we were able to estimate the location of the largest cities in the Middle East and China, respectively (Louwerse, Hutchinson, & Cai, 2012).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The idea is simple: Places that are spatially close to each other co-occur together in language, even when the texts in which they co-occur are not spatial in nature per se. And these findings were not limited to existing cities: Locations in fictional Middle Earth were reliably estimated from the novel The Lord of the Rings, with experimental findings indicating that readers of the novel rely on language statistics in their geographical estimates (Louwerse & Benesh, 2012). Similarly, using Arabic and Chinese texts, we were able to estimate the location of the largest cities in the Middle East and China, respectively (Louwerse, Hutchinson, & Cai, 2012).…”
Section: Introductionmentioning
confidence: 80%
“…As in our other studies (Louwerse, 2011;Louwerse & Benesh, 2012;Louwerse & Zwaan, 2009), we used latent semantic analysis (LSA), a commonly used algorithm that estimates similarities in meaning (Landauer & Dumais, 1997;Landauer, Laham, & Derr, 2004). LSA is a statistical technique that generates vectors representing terms (e.g., words) and documents (e.g., paragraphs).…”
Section: Latent Semantic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, rocca (stronghold) is associated with names of famous Italian castles, like Calascio, Sanvitale, and Torrechiara; however, since Rocca is also the surname of the Alpine skier Giorgio Rocca, it also produces as neighbors names of other athletes, like Raich (Benjamin Raich, also Alpine skier), Schoenfelder (Olivier Schoenfelder, ice dancer), and Rivellino (Roberto Rivellino, football player). To a certain extent, also geographical information is captured in the model (in line with the results by Louwerse & Benesh, 2012). The neighbors of Belgio (Belgium) are either surrounding countries (Francia -France, Olanda -Netherlands, Germania -Germany) or Belgian cities (Namur, Charleroi).…”
Section: Qualitative Analysismentioning
confidence: 96%
“…The majority of studies (6) indicate that sketch maps based on a real map are better than those based on a text [114][115][116][117]. Only one study failed to confirm this conclusion, finding no difference between the use of a map and a text [118]. One study confirmed that both a map and a text had a positive impact [119].…”
Section: Groupmentioning
confidence: 99%